2022
DOI: 10.1186/s13287-022-02942-9
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal ligament stem cells as a promising therapeutic target for neural damage

Abstract: Background The damaged neuronal cells of adult mammalian lack the regenerative ability to replace the neuronal connections. Periodontal ligament stem cells (PDLSCs) are the promising source for neuroregenerative applications that can improve the injured microenvironment of the damaged neural system. They provide neuronal progenitors and neurotrophic, anti-apoptotic and anti-inflammatory factors. In this study, we aimed to comprehensively explore the various neuronal differentiation potentials o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…This immunophenotype profile, recognized as a hallmark of multipotency, highlights the differentiation potential of hPDLSCs into various lineages such as chondrocytes, neural cells, cardiomyocytes, and mostly osteoblasts and cementoblasts which are implied in sustaining the formation of new bone [18][19][20]. In addition, hPDLSCs exert a strong paracrine capacity by releasing several angiogenic, mitogenic, antiapoptotic, anti-inflammatory and antioxidative factors, which together are proposed as the main mechanisms in regulating tissue repair upon MSC transplantation [16,[21][22][23][24][25].…”
Section: Hpdlscs As Therapeutic Tool: Current Statusmentioning
confidence: 87%
See 1 more Smart Citation
“…This immunophenotype profile, recognized as a hallmark of multipotency, highlights the differentiation potential of hPDLSCs into various lineages such as chondrocytes, neural cells, cardiomyocytes, and mostly osteoblasts and cementoblasts which are implied in sustaining the formation of new bone [18][19][20]. In addition, hPDLSCs exert a strong paracrine capacity by releasing several angiogenic, mitogenic, antiapoptotic, anti-inflammatory and antioxidative factors, which together are proposed as the main mechanisms in regulating tissue repair upon MSC transplantation [16,[21][22][23][24][25].…”
Section: Hpdlscs As Therapeutic Tool: Current Statusmentioning
confidence: 87%
“…Stem cells populating PDL reside in the perivascular space of the periodontium and contain 95% of mesenchymal stem cells and 5% of neural crest stem cells, according to their embryonic origin from ectomesenchyme [15,16]. Nowadays, mesenchymal stem cells are revolutionizing the field of oral diseases, representing a potential tool for periodontal regeneration [17].…”
Section: Hpdlscs As Therapeutic Tool: Current Statusmentioning
confidence: 99%
“…Exosomes (EXs), one small particule of extracellular vesicles (usually 40–120 nm in diameter), containing many bioactive macromolecules, such as proteins, nucleic acids and lipids involved in biological regulation of cells ( Liu et al, 2021 ). Several previous studies demonstrated MSC-derived EXs have the ability to enhance functional recovery in animal model of SCI by reducing cell apoptosis and inflammation response, and promoting angiogenesis ( Liu et al, 2021 ; Mohebichamkhorami et al, 2022 ). Depending on the cell sources, MSC-derived EXs have specific set of proteins and nucleic acids that can promote tissue regeneration.…”
Section: The Potential Mechanisms Of Dpscs In Scimentioning
confidence: 99%
“…However, BMSCs are sourced from bone marrow, which can restrict their availability. In contrast, due to their origin being from the periodontium, PDLSCs are readily available throughout the entire human lifespan, [13,14] and have demonstrated regenerative capacities in multiple tissues, [15][16][17] making them an ideal source of MSCs for the treatment or prevention of alveolar bone loss.…”
Section: Introductionmentioning
confidence: 99%